PENGARUH PENGHINDARAN PAJAK TERHADAP BIAYA HUTANG PASCA PERUBAHAN TARIF PAJAK BADAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nining Purwanti (Jurnal Akuntansi Indonesia, 2014)
The aim of the research is to analyze tax avoidance behavior to cost of debt moderated by tax rates changes, on manufacturing company in Indonesia in 2008-2010. Panel data analysis is used in this research. In this study usingbook tax gap to measure tax avoidance and using the models used by Lim (2010), Dwi Martani (2011) and Widya Sartika (2012) to meansure cost of debt. The study find that tax avoidance has negative influence on cost of debt. Tax avoidance creates a risk thereby increasing the cost of debt. In the period before tax rate reduction the influence of tax avoidance on cost of debt smaller compare after period of tax reduction, this indicates the presence of earning management conducted by the company before tax rate reduction.